PENGARUH MATA KULIAH KEWIRAUSAHAAN DAN LINGKUNGAN KELUARGA TERHADAP MINAT BERWIRAUSAHA MELALUI SELF EFFICACY SEBAGAI VARIABEL INTERVENING PADA MAHASISWA PRODI PENDIDIKAN EKONOMI STAMBUK 2021 UNIVERSITAS NEGERI MEDAN - Sonia Hapsari Marbun; Putri Kemala Dewi Lubis (STKIP Subang, 2024)
This research aims to determine the influence of entrepreneurship courses and family environment on interest in entrepreneurship through self-efficacy as an intervening variable in Stambuk 2021 economic education students at Medan State University. This type of research is ex post facto research. The population in this study was all 2021 Stambuk economic education students, totaling 78 people. The sample used in this research was 78 students taken based on total sampling technique. Data collection techniques were carried out using observation, documentation and questionnaires. Then the classic assumption tests in this research are the normality test, multicollinearity test, and heteroscedasticity test. Hypothesis testing was carried out using linear regression analysis for hypotheses 1,2,3,4 and 5, path analysis and Sobel test for hypotheses 6 and 7 using the SPSS.22 program. The results of the research show that: (1) There is a direct influence between entrepreneurship courses on student self-efficacy (2) There is a direct influence between the family environment on student self-efficacy (3) There is a direct influence between entrepreneurship courses on students' interest in entrepreneurship (4) There is an influence family environment has a direct influence on students' interest in entrepreneurship (5) There is a direct influence of self-efficacy on students' interest in entrepreneurship (6) Self-efficacy is able to mediate the influence of entrepreneurship courses on interest in entrepreneurship (7) Self-efficacy is able to mediate the influence of the family environment on students' interest in entrepreneurship